REPRESSENTASI YOUKAI DALAM ANIME NURARIHYON NO MAGO KARYA HIROSHI SHIBASHII - Widstana Budi Junior, Yogi; Rauh Artana, I Nyoman; Ayu Laksmita Sari, Ida (CV. Lafadz Jaya, 2025)
This research is entitled 'Representation of Youkai in Hiroshi Shiibashi's Anime Nurarihyon No Mago'. The purpose of this research is to describe the representation of Youkai which includes the physical form to the characteristics they have, and also to find out the Bushido value that exists in Youkai in the Anime Nurarihyon No Mago. This research uses descriptive analysis method. The theories used in this research are semiotic theory by Pierce and literary anthropology theory by Sudikan. Based on the results of the analysis, it is known how the representation of Youkai in the Nurarihyon No Mago Anime, namely: 1) Nurarihyon, 2) Yukki onna, and 3) kappa. In addition, Youkai also reflects the Japanese cultural value of Bushido which includes the following concepts: 1) Gi (義) Truth, 2) Yu (勇) Courage, 3) Jin (仁) Virtue, 4) Rei (礼) Courtesy, 5) Makoto (誠) Honesty, 6) Meiyou (名誉) Honor, and 7) Chugi (忠義) Loyalty.